Juridical Analysis of the Double Track System in Countering Terrorism Acts In Indonesia: Analisis Yuridis Terhadap Double Track System Dalam Penanggulangan Tindak Pidana Terorisme Di Indonesia - Kukuh Satria Wiratama; Muhammad Azil Maskur; Shofriya Qanitatin Abidah (Indonesian Journal of Counter Terrorism and National Security, 2025)
Terrorism has become a serious concern crime in Indonesia, where the methods of countering it through law enforcement are currently faced with a number of challenges. Countering terrorism is faced with the situation of rapid development of modern terrorism and the contradiction between the need to handle terrorism as holistically as possible with existing regulations and a shift in the paradigm of modern law. This study aims to analyze the regulation of terrorism crimes in Indonesia from the perspective of a double track system in imposing sanctions. This research is also intended to identify and elaborate on the need to reform the penal policy to counter terrorism through the application of a pattern of imposing sanctions with a double track system for terrorism act. The method used in this study is doctrinal legal reasearch using a statutory approach and conseptual approach. The results obtained through this research are that the double track system has not been used and is firmly stated as a pattern for imposing sanctions for terrorism crimes in Indonesia. Furthermore, the double track system in imposing sanctions for terrorism crimes can be an idea for reforming penal policies in effective and holistic countermeasures of terrorism. The implementation of the double track system is based on the need for the law to respond to the development of terrorism, increase the effectiveness of the Terrorism Law, and adjust the paradigm of modern law.